Open Issue: Covering Real Estate Crisis, Wind Catchers in Iran, Vernacular Architecture Studies, Mass Housing, Translating Memories, Redefining Vernacular, Environment Responsiveness - Wilkinson, Nicholas (Open House Int, 2013)
[Abstract Not Available]